Gestures and looks in medieval narrative - Burrow, J. A. (John Anthony) (Cambridge studies in medieval literature, 2002)
In medieval society, gestures and speaking looks played an even more important part in public and private exchanges than they do today. In this, the first study of its kind in English, John Burrow examines the role of non-verbal communication in a range of narrative texts.